Respuesta :
Answer:
The term to add is
[tex]-\frac{1}{3} x[/tex]
Step-by-step explanation:
Let
b ----> the term to add
we have
[tex]\frac{5}{6}x-4+b=\frac{1}{2} x-4[/tex]
Solve for b
Adds 4 both sides
[tex]\frac{5}{6}x+b=\frac{1}{2} x[/tex]
subtract 5/6x both sides
[tex]b=\frac{1}{2} x-\frac{5}{6}x[/tex]
Remember that
[tex]\frac{1}{2}=\frac{3}{6}[/tex]
substitute
[tex]b=\frac{3}{6} x-\frac{5}{6}x[/tex]
[tex]b=-\frac{2}{6} x[/tex]
Simplify
[tex]b=-\frac{1}{3} x[/tex]
therefore
The term to add is
[tex]-\frac{1}{3} x[/tex]